The effect of increasing the contact surface on tendon healing - Fatma Bilgen; Yakup Duman; Ömer Bulut; Mehmet Bekerecioğlu (Archives of Plastic Surgery, 2018)
Background The most common complication after tendon repair is the development of adhesion, with subsequent rupture.